Genealogías imaginadas: Kymlicka, el multiculturalismo y el liberalismo - Aguilar Rivera, José Antonio (El Colegio de México A.C., 2024)
The article provides a critical account of Will Kymlicka’s theory of multiculturalism and its practical consequences. By questioning its intellectual coherence, the essay calls into question the genealogy of multiculturalism offered by Kymlicka. That account of origins evidences the philosopher’s ambivalence towards universalism. Kymlicka’s multiculturalism is also inconsistent regarding the protection of individual rights from cultural minorities. The article cast doubts on the liberal character of Kymlicka’s theory because he relies on nationalism to devise normative justifications against external enforcement of individual rights. The article assesses the role of multiculturalism in the world and its role in the abandonment of some unfulfilled goals of liberal constitutionalism by providing some evidence from 21st century Colombia